Palladium-Catalyzed Tandem Carbocyclization–Suzuki Coupling Reactions of Trifluoromethyl-Containing Building Blocks Leading to 2-Trifluoromethylindenes - Wang, Wen-Ying; Sun, Lei-Lei; Deng, Chen-Liang; Tang, Ri-Yuan; Zhang, Xing-Guo (Synthesis, 2013)
A palladium-catalyzed tandem carbocyclization–Suzuki coupling is described leading to the synthesis of trifluoromethyl-containing indenes in moderate to good yields. The reactions take place in the presence of palladium(II) acetate, a phosphorus-containing ligand [dicyclohexyl(2′,4′,6′-triisopropylbiphenyl-2-yl)phosphine] and potassium carbonate in toluene as the solvent. The process occurs via intramolecular carbocyclization and subsequent Suzuki coupling of the ortho-(2-chlorovinyl)-alkynylbenzenes with arylboronic acids.
Keywords: indene; palladium; trifluoromethyl; carbocyclization; Suzuki coupling